Simplify the given equation.
6 - (3x + 10) + 4(2 - x) = 15

Question

Asked 1/15/2015 2:49:11 PM

Updated 1/15/2015 6:37:25 PM

2 Answers/Comments

Flagged by janezeshun [1/15/2015 5:58:59 PM]

Question

Asked 1/15/2015 2:49:11 PM

Updated 1/15/2015 6:37:25 PM

2 Answers/Comments

Flagged by janezeshun [1/15/2015 5:58:59 PM]

Rating

3

6 - (3x + 10) + 4(2 - x) = 15

6 - 3x - 10 + 8 - 4x = 15

-7x + 4 = 15

-7x = 11

x = -7/11

6 - 3x - 10 + 8 - 4x = 15

-7x + 4 = 15

-7x = 11

x = -7/11

Added 1/15/2015 5:59:55 PM

This answer has been flagged as incorrect.

Flagged by andrewpallarca [1/15/2015 6:37:27 PM]

3

6 - (3x + 10) + 4(2 - x) = 15;

(-3x - 4) + (8 - 4x) = 15;

-7x + 4 = 15;

-7x = 15 - 4;

-7x = 11;

x = -11/7

(-3x - 4) + (8 - 4x) = 15;

-7x + 4 = 15;

-7x = 15 - 4;

-7x = 11;

x = -11/7

Added 1/15/2015 6:37:25 PM

This answer has been confirmed as correct and helpful.

Simplify the given equation.
5x + 2(x - 3) = -2(x - 1) **Weegy:** 5x + 3(x - 2) = -2(x + 1); 5x + 3x - 6 = -2x - 2; 8x - 6 = -2x - 2; 8x + 2x = -2 + 6; 10x = 4; x = 4/10; x = 2/5 (More)

Question

Updated 1/15/2015 5:55:07 PM

1 Answer/Comment

5x + 2(x - 3) = -2(x - 1)

5x + 2x - 6 = -2x + 2

7x - 6 = -2x + 2

7x + 2x = 2 + 6

9x = 8

x = 8/9

5x + 2x - 6 = -2x + 2

7x - 6 = -2x + 2

7x + 2x = 2 + 6

9x = 8

x = 8/9

Added 1/15/2015 5:55:07 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/15/2015 6:32:30 PM]

can you solve for x? 3(x + 2) = 12 User: Can you Solve for x?
5(x - 3) + 4(x + 3) = 3(x - 1)
**Weegy:** 5(x - 3) + 4(x + 3) = 3(x - 1) 5x - 15 + 4x + 12 = 3x - 3; 5x + 4x - 3x = -3 - 12 + 15; 6x = 0; x = 0 **User:** Can you Solve for x?
5(x + 1) = 4(x + 8) (More)

Question

Updated 1/15/2015 6:24:18 PM

2 Answers/Comments

3(x + 2) = 12

3x + 6 = 12

3x = 12 - 6

3x = 6

x = 6/3

x = 2

3x + 6 = 12

3x = 12 - 6

3x = 6

x = 6/3

x = 2

Added 1/15/2015 6:19:10 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/15/2015 6:25:05 PM]

5(x + 1) = 4(x + 8)

5x + 5 = 4x + 32

5x - 4x = 32 - 5

x = 27

5x + 5 = 4x + 32

5x - 4x = 32 - 5

x = 27

Added 1/15/2015 6:20:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/15/2015 6:25:44 PM]

29,307,940

questions answered

There are no comments.